1988
DOI: 10.1071/sr9880391
|View full text |Cite
|
Sign up to set email alerts
|

The effects of soil water content and bulk density on the compactibility and soil penetration resistance of some Western Australian sandy soils

Abstract: Quantitative models to predict the effects of soil compaction on wheat yields are being developed for the northern sandplains of Western Australia. An understanding of the relationships between soil water content (W), bulk density (p), compactibility and soil penetration resistance (P) is required. Thirteen subsoils from W.A. sandplain soils were tested for compactibility. As the amounts of very coarse sand or clay in the soil increased, the maximum density (�max.) achieved with a standard compactive effort al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 0 publications
2
27
0
4
Order By: Relevance
“…O comportamento desses modelos, em ambos os casos, evidencia relação diretamente proporcional com o aumento dos teores de argila e matéria orgânica, resultando em maiores teores de água no solo, em uma função que tende à estabilização, no primeiro caso, e em comportamento linear, no segundo. Por outro lado, solos com maior teor de argila e matéria orgânica tendem a apresentar valores maiores para a capacidade de campo (BRADY & WEIL, 2001), o que aumenta a quantidade de água necessária para alcançar o teor citado por HENDERSON et al (1988), de 70% da capacidade de campo, no qual a diminuição da água aumenta exponencialmente a sua influência na resistência do solo à penetração. Tal situação é indicativa de que não se pode tecer considerações conclusivas a respeito da menor influência no IC, na região com maior teor de água, a qual também apresenta maior teor de argila e de matéria orgânica.…”
Section: Resultsunclassified
“…O comportamento desses modelos, em ambos os casos, evidencia relação diretamente proporcional com o aumento dos teores de argila e matéria orgânica, resultando em maiores teores de água no solo, em uma função que tende à estabilização, no primeiro caso, e em comportamento linear, no segundo. Por outro lado, solos com maior teor de argila e matéria orgânica tendem a apresentar valores maiores para a capacidade de campo (BRADY & WEIL, 2001), o que aumenta a quantidade de água necessária para alcançar o teor citado por HENDERSON et al (1988), de 70% da capacidade de campo, no qual a diminuição da água aumenta exponencialmente a sua influência na resistência do solo à penetração. Tal situação é indicativa de que não se pode tecer considerações conclusivas a respeito da menor influência no IC, na região com maior teor de água, a qual também apresenta maior teor de argila e de matéria orgânica.…”
Section: Resultsunclassified
“…Significant soil particle rearrangement hence becomes problematic (Whalley et al, 2005) and the friction experienced by the penetrologger cone increases rapidly. Henderson et al (1988), Vaz et al (2001) and Ampoorter et al (2007) also stated this positive relationship, and reported a logarithmic shape. Although BD remains more or less constant at higher values, PR may still increase.…”
Section: Relationship Between Bulk Density and Penetration Resistancementioning
confidence: 97%
“…Henderson et al (1988), Smith et al (1997), Vaz et al (2001) and Whalley et al (2005), for a wide variety of textural classes ranging from sand to clay. The non-linear behaviour can be explained by the pore space being reduced as bulk density increases.…”
Section: Correlation Between Bulk Density and Penetration Resistancementioning
confidence: 99%